Inclusive Education Management in Social Studies Course of Children with Special Needs - Ahmad Samawi (Journal of ICSAR, 2017)
This study aimed at describing the implementation of inclusive education at the social studies course (IPS/Ilmu Pengetahuan Sosial) in the Department of Special Education. The method used was qualitative in term of case studies. The research subject was the student of Special Education Department consisting of four blind students and 60 regular students. The instrument used was the observation, interviews and documentation. The mechanical analysis of data validity was triangulation. The result found that the inclusive education was not difficult to apply well in the IPS course. Students’ learning activities in the classroom were very dynamic discussion about the IPS subject and the IPS learning practices in the micro class. The visually impaired student results were not inferior for regular students. It was concluded that inclusive education can be well applied in the IPS course